Virtual surgical telesimulations in otolaryngology (2005)
Distance learning can be enhanced with the use of virtual reality; this paper describes the design and initial validation of aWeb Environment for Surgery Skills Training on Otolaryngology (WESST-OT). WESST-OT was created aimed to help trainees to gain the skills required in order to perform the Functional Endoscopic Sinus Surgery procedure (FESS), since training centers and specialist in this knowledge are scarce in Colombia; also, it is part of a web based educational cycle which simulates the stages of a real procedure. WESST-OT is one from the WESST family of telesimulators which started to be developed from an architecture proposed at the Medicine Meets Virtual Reality conference 2002; also, it is a step towards the use of virtual reality technologies in Latin America.